The Zinc Finger Protein Mig1 Regulates Mitochondrial Function and Azole Drug Susceptibility in the Pathogenic Fungus Cryptococcus neoformans - Mélissa Caza (American Society for Microbiology, 2016)
ABSTRACT The opportunistic pathogen Cryptococcus neoformans causes fungal meningoencephalitis in immunocompromised individuals. In previous studies, we found that the Hap complex in this pathogen represses genes encoding mitochondrial respiratory functions and tricarboxylic acid (TCA) cycle components under low-iron conditions. The orthologous Hap2/3/4/5 complex in Saccharomyces cerevisiae exerts a regulatory influence on mitochondrial functions, and Hap4 is subject to glucose repression via the carbon catabolite repressor Mig1. In this study, we explored the regulatory link between a candidate ortholog of the Mig1 protein and the HapX component of the Hap complex in C. neoformans. This analysis revealed repression of MIG1 by HapX and activation of HAPX by Mig1 under low-iron conditions and Mig1 regulation of mitochondrial functions, including respiration, tolerance for reactive oxygen species, and expression of genes for iron consumption and iron acquisition functions. Consistently with these regulatory functions, a mig1Δ mutant had impaired growth on inhibitors of mitochondrial respiration and inducers of ROS. Furthermore, deletion of MIG1 provoked a dysregulation in nutrient sensing via the TOR pathway and impacted the pathway for cell wall remodeling. Importantly, loss of Mig1 increased susceptibility to fluconazole, thus further establishing a link between azole antifungal drugs and mitochondrial function. Mig1 and HapX were also required together for survival in macrophages, but Mig1 alone had a minimal impact on virulence in mice. Overall, these studies provide novel insights into a HapX/Mig1 regulatory network and reinforce an association between mitochondrial dysfunction and drug susceptibility that may provide new targets for the development of antifungal drugs. IMPORTANCE Fungal pathogens of humans are difficult to treat, and there is a pressing need to identify new targets for antifungal drugs and to obtain a detailed understanding of fungal proliferation in vertebrate hosts. In this study, we examined the roles of the regulatory proteins Mig1 and HapX in mitochondrial function and antifungal drug susceptibility in the fungus Cryptococcus neoformans. This pathogen is a particular threat to the large population of individuals infected with human immunodeficiency virus (HIV). Our analysis revealed regulatory interactions between Mig1 and HapX, and a role for Mig1 in mitochondrial functions, including respiration, tolerance for reactive oxygen species, and expression of genes for iron consumption and iron acquisition functions. Importantly, loss of Mig1 increased susceptibility to the antifungal drug fluconazole, which is commonly used to treat cryptococcal disease. These studies highlight an association between mitochondrial dysfunction and drug susceptibility that may provide new targets for the development of antifungal drugs.